The Fight against Infection and Pain: Devil’s Claw (Harpagophytum procumbens) a Rich Source of Anti-Inflammatory Activity: 2011–2022 - Nomagugu Gxaba; Madira Coutlyne Manganyi (Molecules, 2022)
Harpagophytum procumbens subsp. procumbens (Burch.) DC. ex Meisn. (Sesame seed Family—Pedaliaceae) is a popular medicinal plant known as Devil’s claw. It is predominantly distributed widely over southern Africa. Its impressive reputation is embedded in its traditional uses as an indigenous herbal plant for the treatment of menstrual problems, bitter tonic, inflammation febrifuge, syphilis or even loss of appetite. A number of bioactive compounds such as terpenoids, iridoid glycosides, glycosides, and acetylated phenolic compounds have been isolated. Harpagoside and harpagide, iridoid glycosides bioactive compounds have been reported in countless phytochemical studies as potential anti-inflammatory agents as well as pain relievers. In-depth studies have associated chronic inflammation with various diseases, such as Alzheimer’s disease, obesity, rheumatoid arthritis, type 2 diabetes, cancer, and cardiovascular and pulmonary diseases. In addition, 60% of chronic disorder fatalities are due to chronic inflammatory diseases worldwide. Inflammation and pain-related disorders have attracted significant attention as leading causes of global health challenges. Articles published from 2011 to the present were obtained and reviewed in-depth to determine valuable data findings as well as knowledge gaps. Various globally recognized scientific search engines/databases including Scopus, PubMed, Google Scholar, Web of Science, and ScienceDirect were utilized to collect information and deliver evidence. Based on the literature results, there was a dramatic decrease in the number of studies conducted on the anti-inflammatory and analgesic activity of Devil’s claw, thereby presenting a potential research gap. It is also evident that currently in vivo clinical studies are needed to validate the prior massive in vitro studies, therefore delivering an ideal anti-inflammatory and analgesic agent in the form of H. procumbens products.